Synergizing Scrum and Risk Management to Improve Project Success (Study on Technology Startup PT XYZ) - Sunu Dias Widhi Kurniadi; Slamet Riyadi; Fausta Ari Barata (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
In the dynamic and exciting technology startup industry uncertainty , management project device soft need approach adaptive and responsive to risk . This study explores synergy between Scrum methods and management risk in increase success project at PT XYZ, a startup that implements the Agile-Waterfall hybrid model. Qualitative methods with studies case and analysis descriptive used for digging practice management integrated risk informally in Scrum processes, such as Sprint planning and retrospectives, with support tool collaborative such as Trello and spreadsheets. The results show This synergy increases identification and mitigation risk , collaboration team , and success project in a way technical and managerial . However , the challenges Still found in the documentation risks and the roles of the Scrum Master and Product Owner that need to be considered reinforced . This study recommends development documentation more standardized risks and strengthening role the key to increasing Agile maturity and resilience projects in the technology startup environment